Adaptacja i porozumienie. Komunikacja dwujęzyczna w Europie Środkowej - Hofmański, Wojciech (Slavia Occidentalis, 2019)
Depending on the selected theoretical concept, Central Europe is a melting pot of several or over a dozen linguistic cultures which constantly interacted in the process of historical development. In this multi-national landscape, the presence of Slavs (Czechs, Poles, Slovaks as well as Lusatians, Kashubians or Lemkos) has been a constant element. The speakers have used two languages in a single act of communication which is a phenomenon of its own. This understanding is a tempting area of linguistic research. This text is dedicated to bilingual communication of Slavs with special emphasis placed on the processes of adaptation based on obtaining information from texts in written language (the seven sieves technique).